2017
DOI: 10.1371/journal.pone.0169001
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin-English Bilinguals Process Lexical Tones in Newly Learned Words in Accordance with the Language Context

Abstract: Previous research has mainly considered the impact of tone-language experience on ability to discriminate linguistic pitch, but proficient bilingual listening requires differential processing of sound variation in each language context. Here, we ask whether Mandarin-English bilinguals, for whom pitch indicates word distinctions in one language but not the other, can process pitch differently in a Mandarin context vs. an English context. Across three eye-tracked word-learning experiments, results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 51 publications
4
37
1
Order By: Relevance
“…This study continues a line of research begun by Quam and Creel (2017a), who found that native Mandarin speakers who have become English dominant show attrition in their ability to access lexical tone information. Quam and Creel offered two explanations for their finding.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study continues a line of research begun by Quam and Creel (2017a), who found that native Mandarin speakers who have become English dominant show attrition in their ability to access lexical tone information. Quam and Creel offered two explanations for their finding.…”
Section: Introductionsupporting
confidence: 79%
“…In an event-related potential (ERP) study of neural responses to speech, Schirmer, Tang, Penney, Gunter, and Chen, (2005) found that altering the rime (the central vowel and possibly the last consonant of a word) of an anticipated word created the same N400 ERP (the "confusion" response) as altering the tone of the anticipated word, implying that tones play just as important a role in identifying words in a speech stream as segments. Taken together, Malins and Joanisse (2010) and Schirmer et al (2005) challenge the first explanation put forward in Quam and Creel (2017a): that lexical tone is more prone to attrition because of how the brain stores and accesses this information.…”
Section: Lexical Tonesmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, at the theoretical level, our current findings shed light on the mechanism of pitch processing. A large but under-researched theoretical debate in the literature of Speech Perception is whether the processing of pitch contours during word recognition is language context sensitive [67,68]. Here, language context could be the language mode of communication (e.g., the language of the conversation) or some specific acoustic-phonetic cues within a word or sentence.…”
Section: Discussionmentioning
confidence: 99%
“…Classroom teaching situation is good or bad, directly affecting the quality of fostering talents [2]. General education curriculum is the key factor for implementing general education ideas and goals.…”
Section: Introductionmentioning
confidence: 99%